The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4028/www.scientific.net/kem.359-360.404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nozzle Type and Abrasive on Machinablity in Micro Abrasive Air Jet Machining of Glass

Abstract: Micro abrasive jet machining (MAJM) is a high effective economical technology for three dimensional micro structure fabrications of brittle materials. It is widely used in the fabrication of semiconductors, electronic devices, micro electro-mechanical systems (MEMS), optical-electronic and optical devices, and medical instruments. In this paper, based on the experimental study of MAJM for glass, the influences of the nozzle type/size and abrasive type on the material erosion rate and structure profile are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Machining Process. The drilling process of MASJ is similar to that of micro abrasive blasting [7,8]. Through online observation of the glass drilling process, we found that the interaction between the jet stream and the glass surface have much more effect on the shape of machined holes.…”
Section: Resultsmentioning
confidence: 80%
“…Machining Process. The drilling process of MASJ is similar to that of micro abrasive blasting [7,8]. Through online observation of the glass drilling process, we found that the interaction between the jet stream and the glass surface have much more effect on the shape of machined holes.…”
Section: Resultsmentioning
confidence: 80%
“…Afterwards, the speed remains steady for a while and then reduces. As the stand-off distance further increases, jet diffusion becomes more significant and eventually when at certain stand-off distance, the machining efficiency decreases [3,6]. It can also be noticed from the machined profiles that a low stand-off distance results in small taper angles.…”
Section: Resultsmentioning
confidence: 92%
“…Considerable research and development efforts have been made to study this micromachining process with a view to improve its cutting performance [2][3][4][5]. An understanding of the characteristics of profiles produced in AJM is important in order to control the shape of patterned microstructures [6][7][8]. However, the technology for micromachining using micro abrasive jet with air as the flow medium is still under development and its many aspects are yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium oxide particles with the nominal diameter of 27 mm were used. The density of the particles was 3.95 g/cm 3 and the hardness 14.1 GPa. Five process variables that have been found from previous studies [4,13,14,[23][24][25] to have a profound effect on the machining performance in AJM and AWJ machining were considered in the experiment, which included air pressure, jet impact angle, nozzle traverse speed, abrasive mass flowrate, and nozzle diameters.…”
Section: Experimental Workmentioning
confidence: 99%
“…Although their work involved a reasonable range of process parameters, due to the technology limitation at that time, the nozzle diameters used were relatively large. In a recent work by Fan et al [3], an experimental study was undertaken to understand the effects of particle material on the machinability of glass under different nozzle diameters. Other experimental studies have also been conducted, as have been reviewed by Fan et al [4] and Moridi et al [5].…”
Section: Introductionmentioning
confidence: 99%